Al-Baghdadi’s Usul al-Din: Analyzing Epistemological Themes - Ryandi Ryandi; Amroeni Drajat; Sukiman Sukiman (TSAQAFAH, 2025)
Al-Baghdādī holds a significant position within the early Ash‘ari epistemological tradition. His work, Usul al-Dīn, offers a systematic explanation of the foundational principles of Sunni belief, integrating an epistemological framework that draws from both the Ash‘ari intellectual tradition and the broader Islamic intellectual heritage. This study employs qualitative textual analysis of Usul al-Dīn, focusing primarily on how Al-Baghdādī articulates various epistemological concepts. Several themes are explored within the text, including the definition, classification, and sources of knowledge. The analysis reveals that Al-Baghdādī places knowledge as the foundational principle in his theological discussions. Through his structured and profound approach, Al-Baghdādī views epistemology as an essential tool for resolving theological issues, providing a rational foundation for understanding Islamic faith. This focus on epistemology not only lays the groundwork for the further development of Ash‘ari thought but also solidifies the position of Ilm al-Kalam as a rational and systematic discipline. By critically engaging with various foreign epistemologies, Al-Baghdādī not only strengthens Islamic theological arguments but also expands the intellectual horizons of Islamic theology itself.